(untitled) (The Pakistan Development Review, 1979)
Short-run money demand functions are estimated and elasticities of price expectations and real cash balance adjustment arc determined. By examining the hypothesis that inflation m Nigeria is self-generating, the study concludes that explanations for the rise in price level should be sought in factors other than money supply alone.